(untitled) (مجلة المنصور, 2023)
Materials requirement planning (MRP) is a widely used method for production planning and scheduling. MRP module allows for more efficient and effective use of resources. MRP is a method to determine what, when, and how much component and material are required to satisfy a production plan of end products over time. A MRP system requires a great deal of information and processes in order to perform its complete logic.